UPAYA MENGONTROL TEKANAN DARAH DENGAN LATIHAN SLOW DEEP BREATHING PADA PENDERITA HIPERTENSI - Mahundingan, Rosari Oktaviana; Ramadhani, Dwi Yuniar; Yunita, Irma; Rini, Nurlita Arinda; Risvy, Berliani Ananda (PPM STIKES Adi Husada, 2023)
Introduction & Aim: Hypertension or high blood pressure is a major risk factor in atherosclerosis, cardiovascular disease, heart failure, stroke, and kidney failure. Hypertension is a big and serious problem because it often goes undetected even though it has been years. One of the non-pharmacological therapies that people can do with hypertension is relaxation. Slow Deep Breathing is a relaxation technique that serves to lower blood pressure so that it can be carried out independently. This community service aims to reduce blood pressure in hypertension patients through Slow Deep Breathing exercises. Method of Activity: The methods carried out in community service are health counseling and the demonstration of Slow Deep Breathing exercises. The target of this activity was hypertension patients who were in Balai RT 06 Jalan Gembong Sekolahan which amounted to 23 participants. Results: A total of 23 participants the result showed that characteristics based on gender, the majority were female (87%); based on age, the majority 36-45 years (35%); based on education, the majority were elementary school (43%); and based on work the majority housewife (52%). Characteristics based on long-suffering from hypertension mostly within 2 years (26%). The result of activity before Slow Deep Breathing systolic blood pressure in the stage 2 hypertension category (61%) and after intervention in the stage 1 hypertension category (70%). Discussion: For participation with hypertension, Slow Deep Breathing should be a complementary therapy to monitoring blood pressure to improve the quality of life.